Eighth-Grade Students’ Interest in Writing Descriptive Texts: A Descriptive Quantitative Study - Nuraini; Samsul Amri; Sri Erma Purwanti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Writing is a crucial skill in English language learning, yet students often exhibit low interest in this activity. This study aimed to investigate eighth-grade students' interest in writing descriptive texts, focusing on five key indicators: feeling, attention, attraction, active involvement, and persistence. Employing a descriptive quantitative design, this study involved all 28 eighth-grade students at MTs Tarbiyah Islamiyah Sei Simbar selected through total sampling. Data were collected using a 15-item Likert-scale questionnaire and analyzed using percentage analysis. The findings revealed that the students’ overall interest in writing descriptive texts was low, with an average score of 35.28%. Specifically, the percentage for each indicator was 37.85% for feeling, 35.47% for persistence, 34.52% for attraction, 34.52% for active involvement, and 34.04% for attention. These results indicate a general lack of engagement and focus during descriptive writing tasks. Consequently, English teachers are highly encouraged to implement more innovative, interactive, and visually engaging instructional strategies to foster students' motivation and active participation in writing activities.